Answer:
x=6+1
Step-by-step explanation:
Answer:
81/4
Step-by-step explanation:
I know this because I did this before
Answer:
Part 1) ![FG=4.4\ units](https://tex.z-dn.net/?f=FG%3D4.4%5C%20units)
Part 2) ![EF=3.9\ units](https://tex.z-dn.net/?f=EF%3D3.9%5C%20units)
Part 3) ![m\angle G=63^o](https://tex.z-dn.net/?f=m%5Cangle%20G%3D63%5Eo)
Step-by-step explanation:
step 1
Find the measure of length side FG
In the right triangle EFG
we know that
----> by SOH (opposite side divided by the hypotenuse)
substitute the given values
![sin(27^o)=\frac{2}{FG}](https://tex.z-dn.net/?f=sin%2827%5Eo%29%3D%5Cfrac%7B2%7D%7BFG%7D)
![FG=\frac{2}{sin(27^o)}=4.4\ units](https://tex.z-dn.net/?f=FG%3D%5Cfrac%7B2%7D%7Bsin%2827%5Eo%29%7D%3D4.4%5C%20units)
step 2
Find the measure of length side EF
In the right triangle EFG
we know that
----> by CAH (adjacent side divided by the hypotenuse)
substitute the given values
![cos(27^o)=\frac{EF}{4.4}](https://tex.z-dn.net/?f=cos%2827%5Eo%29%3D%5Cfrac%7BEF%7D%7B4.4%7D)
![EF=cos(27^o)(4.4)=3.9\ units](https://tex.z-dn.net/?f=EF%3Dcos%2827%5Eo%29%284.4%29%3D3.9%5C%20units)
step 3
Find the measure of angle G
we know that
---> by complementary angles in a right triangle
![m\angle G=90^o-27^o=63^o](https://tex.z-dn.net/?f=m%5Cangle%20G%3D90%5Eo-27%5Eo%3D63%5Eo)
Answer: p = 6
Step-by-step explanation:
HI !
px + 3y - ( p-3)=0
a₁ = p , b₁ = 3 , c₁ = - (p-3)
=====================
12x + py - p=0
a₂ = 12 , b₂ = p , c₂ = -p
since , the equations have infinite solutions ,
a₁/a₂ = b₁/b₂ = c₁/c₂
p/12 = 3/p = p-3/p
--------------------------------------
p/12 = 3/p
cross multiply ,
p² = 36
p = √36
p = 6
for the value of p = 6 , the equations will have infinitely many solutions
Answer:
0.33...acre
Step-by-step explanation:
1/4=0.25
3/4=0.75
-------------
0.25/0.75=x/1
cross product
0.75*x=0.25*1
0.75x=0.25
x=0.25/0.75
x=0.3